Massive Open Online Course (MOOC) Readiness of Pangasinan State University – Open University Systems Students - Queroda, Phillip G. (International Journal on Open and Distance e-Learning, 2019)
This study was conducted to determine the readiness of PSU-OUS students in Massive Open Online Course (MOOC) before its implementation in the institution. MOOC is an innovative online course available for anyone. It “provides an affordable and flexible way to learn new skills, advance student’s career, and deliver quality educational experiences” (Mooc.org, 2009; Veermata Jijabai Technological Institute (VJTI, n.d. p.1) being utilized by prestigious institutions like UPOU and SEAMEO INNOTECH. Hence, MOOC’s fusion to the different courses in PSU-OUS is promising and something to look forward to. The research used the descriptive method and the respondents were chosen through purposive sampling technique. To analyze and interpret the data gathered, the researcher used the weighted mean. The majority of the students of PSU-OUS are female and are working in the government. Many of the respondents have less exposure to seminars relating to distance learning education while mostly of them are 21 – 30 years old, taking up Master of Arts in Education major in Educational Management and are receiving 21 – 30 thousand monthly. The results reflected that students are slightly ready in downloading or installing programs or plugins such as Java, Adobe, Reader, Quick Time and etc., and they are also slightly ready in using Learning Management System like iFolio, SPIN, and Moodle. However, the results also showed that students are prepared on various aspects such as technology access, online skills, motivation, online audio/video and internet discussions. Therefore, the students of PSU-OUS are ready in the implementation of MOOC in the university.